Gerard Duggan's school reports - Duggan, Éamonn, 1874-1936; Duggan, May (1933)
School reports for Gerard Duggan, issued by St. Dominic's Preparatory College, Cabra and Blackrock College. Also included is a school certificate issued by Blackrock College and an attached envelope addressed to his mother Mrs. May Duggan at her home in Seapoint, Co. Dublin.
Gerard Duggan was the son of Cumann na nGaedhael politician and solicitor Éamonn (Edmund) Duggan and his wife May Duggan (née Kavanagh).
Keywords: Duggan, Gerard